Comparison of Protein Concentration in Red and White Muscles in Two Species of Bony Fish (Baghdad Science Journal, 2022)
The current study deals with estimating the protein concentration and the effect of fish weight on protein concentration values in red and white muscles in two different regions ( R1 : Anterior region lies 2 cm behind the head and R2: posterior region lies 2cm from caudal fin (in two types of bony fish, namely common carp (Cyprinus carpio) and Nile tilapia (Oreochromis niloticus). Samples were collected from Karmat Ali river- north of Basrah between October 2019 and February 2020. The protein was extracted using protein extraction buffer, the current study show that the average of protein concentration in red muscles of Nile tilapia ranged between 7.74-7.4 mg / ml and ( 6.8-8.85 mg / ml) in R1 and R2 region respectively, while it ranged between 173-334 mg / ml and 127-253 mg / ml in R1and R2 region in white muscles, respectively. In Carp, protein concentration for red muscles was 7.19-9.10 mg / ml and 6.87-8.41 mg / ml in R1 and R2 regions, respectively. On the other hand, protein concentration in white muscles ranged between 98.7-250.2 mg / ml and 61.5-214.1 mg / ml in both R1 and R2 regions respectively. The statistical analysis results of the protein concentration in the red and white muscles in the body regions indicated that there was a significant difference(P<0.05) and non- significant difference (P>0.05) between the protein concentration in red and white muscles in the studied species ,The current study concluded that white muscles contain a higher protein concentration than red muscles and that weight gain has a significant effect on protein concentration in white muscles.